Mais Contigo’s Project: Associated factors with depressive symptoms, resilience and coping among high school students (Research, Society and Development, 2022)
This study investigated factors associated with depressive symptoms, resilience and coping among high school students and analyzed whether these outcomes differed between students who participated or not in the Mais Contigo project. This project is responsible for promoting mental health and preventing suicide developed in the school environment. A quantitative study was conducted in 2018 with 123 adolescents through a socio-demographic survey, the Resilience scale, Major Depression Inventory and Coping strategies inventory. The data were analyzed using descriptive statistics, association and correlation tests. Students who participated of Mais Contigo’s Project used the Coping strategy “Acceptance of responsibility”, which had positive correlations with resilience. Depressive symptoms were associated with life and sleep dissatisfaction, lack of leisure, lack of mental health diagnosis and lower resilience. Resilience was associated with satisfaction with life, leisure, lack of mental health disorder, less depressive symptoms and more coping. Coping was associated with satisfaction with life, leisure and the year of high school. It is important to develop and evaluate actions that focus on factors that have shown as promising for the development of coping, resilience and reduction of depressive symptoms. It is noteworthy that the Mais Contigo Project covers many of these factors.